Insights into Ceres's evolution from surface composition. (12th August 2018) - Castillo‐Rogez, Julie; Neveu, Marc; M Sween, Harry Y.; Fu, Roger R.; Toplis, Michael J.; Prettyman, Thomas
Abstract: Inspired by the recent results of the Dawn mission, thermodynamic models of rock alteration and brine evaporation have been used to help understand the conditions under which water–rock interaction took place within the dwarf planet Ceres. This analysis constrains Ceres's early history and offers a framework within which future observations may be interpreted. A broad range of alteration conditions have been simulated using the Geochemist's Workbench and PHREEQC software, associated with the FREZCHEM model that constrains the consequences of freezing the liquid phase in equilibrium with the observed mineralogical assemblage. Comparison of the modeling results with observed surface mineralogy at Ceres indicates advanced alteration under a relatively high fugacity of hydrogen, a conclusion that is consistent with predictions for, and observations of, large ice‐rich bodies. The simulations suggest production of methane that could help regulate the redox environment and possibly form clathrate hydrates upon freezing of the early ocean. The detection of localized occurrences of natrite (sodium carbonate) at the surface of Ceres provides key constraints on the composition of fluids that are necessarily alkaline. In addition, the combined hydrothermal and freezing simulations suggest that hydrohalite may be abundant in Ceres's subsurface, similar to Earth's polar regions. The global homogeneity of Ceres's surface, made of material formed at depth, suggests a large‐scale formation mechanism, while local heterogeneities associated with impact craters and landslides suggest that some form of sodium carbonate and other salts are accessible in the shallow subsurface.